The Ochteridae of Ecuador, with new records and an identification key (Hemiptera: Heteroptera: Nepomorpha) - Cianferoni, Fabio (Zootaxa, 2012)
Two species of Ochteridae, Ochterus manni Hungerford, 1927 and O. viridifrons (Champion, 1901) are recorded for thefirst time from Ecuador, so that thus six species belonging to the genus Ochterus Latreille, 1807 and one to the genusOcyochterus Drake & Gómez-Menor, 1954 are now recorded from Ecuador. A remark on the endemic O. unidentatusChen & Nieser, 1992, a checklist of the Ochteridae of Ecuador, and an identification key to the Ecuadorian species are provided.